PEMIKIRANPENDIDIKANISLAMS.M.NAL-ATTAS - Raudho Zaini (LPPM STAI Raudhatul Akmal, 2023)
The thoughts of figures about Islamic education are very interesting to study.Because discussing the thoughts of figures will become a reference needed to answercurrent and future educational problems. The purpose of this study is to find out theconcept of Islamic education according to S.M.Nal-Attas. The type of research used islibrary research and the method used is descriptive qualitative research to present thethought of Islamic education by S.M.Nal-Attas briefly and concisely. The approachused is a pragmatic approach with two sources of data, namely primary and secondary.Primary data is data obtained from the original works of S.M.Nal-Attas and secondarydata sources are data obtained from relevant books, articles published in accreditedjournals, as well as writings of papers that cover the topic of peace of mind Islamiceducation S.M.Nal-Attas. Data collection used a literature study technique which wasthen analyzed. The results of the research in this paper are concluded, among others (1)the concept of education is Islamic values which are based on sources from the Al-Qur`an, Hadith, and ijtihad of scholars (2) the concept of Islamic education put forwardby S.M.Nal-Attas namely the meaning its substance and essence is the word ta`dib,because the word ta`dib includes the meaning of teaching, upbringing, knowledge, andalso education. The educational method used by S.M.Nal-Attas is the tauhid methodandthe story method.